Automated software package for selecting transport technology for grain transportation by road freight transport - V. Tsopa; T. Bilko; S. Cheberyachko; O. Deryugin; B. Hrymalo (Machinery & Energetics)
The aim of the work was to develop a software package for making a management decision to choose a transport technology for grain transportation by road from a set of alternatives. To achieve this goal, the morphological analysis method was used, which is based on selection of possible solutions for individual parts of the task. A software package for making a management decision from a set of alternatives was proposed, which consisted of four modules and four blocks. It was based on two methods: fuzzy Decision-Making Trial and Evaluation Laboratory (hereinafter – fuzzy Dematel) and gray relational analysis (hereinafter – GRA), which are used to determine the basic indicators and, on their basis, select the transport technology for grain transportation itself. The software package implemented an algorithm of eight steps: entering groups of indicators, their pairwise analysis, determining basic indicators based on the total matrix of relationships, entering the values of basic and reference indicators of transport technologies for grain transportation and weight coefficients, constructing gray analysis matrices, determining the index of basic indicators relative to target ones achievement. As a result, the best transport technology for grain freight road transportation was selected to meet the target (reference) indicators of the motor transport enterprise according to the following indicators: load transportation tariff; load transportation speed; diesel fuel consumption per 100 km; load volume; transportation distance; transport process energy intensity; time spent on loading and unloading operations; load safety during transportation; carrier reliability; driver satisfaction with working conditions. According to the calculation results, it was noted that the transport technology for grain transportation best meets the target indicators – load road train with dump semi-trailer. The dependences of the transport technology for load transportation basic indicators and motor transport enterprise target indicators were established, which allows improving the algorithm for making management decision to choose an effective transport technology for transportation from a set of alternative ones. The proposed process of selecting the best solution from a set of alternatives can be used in organisations that select the best technology for road load transportation of bulk cargo – grain